In situ dry matter and fiber fraction degradability of the Mineirão stylos - doi: 10.4025/actascianimsci.v34i2.13138 - Corrêa, Daniel Staciarini; Magalhães, Roberto Toledo de; Siqueira, Domingas Cruvinel Batista de (Acta Scientiarum. Animal Sciences, 2011)
This research evaluated, using the in situ technique, the dry matter and fiber fraction degradability of the Mineirão stylo (Stylozanthes guianensis). The nylon bag method was used for the degradability assay, with two incubations in rumen-cannulated adult female cows. In each incubation, 25 samples of 7.0 g each were used. The samples were collected at 0, 6, 9, 12, 24, 36, 48, 72 and 96 hours. The experiment was conducted according to a randomized blocks design and data were submitted to analysis of variance. The maximum effective degradability was obtained in the 2% passage rate. For the 5% passage rate the Mineirão stylo showed effective degradation of 75.70% for dry matter, 59.01% for neutral detergent fiber and 76.81% for acid detergent fiber. The digestibility achieved by the dry matter and fibrous fraction from Mineirão was considered high. These results, coupled with the low lag time found reveal the forage potential of the cultivar.